A emoção “maquiada” de razão: aspectos prosódicos e argumentativos de uma palestra espírita kardecista - Silva, Rosana Cláudia da (2008)
This dissertation studies the performance of prosodic elements, speech speed and volume, in a kardecist spiritist lecture, a religious doctrinal discourse, in order to learn about their argumentative working towards persuasion. The audio recording of the lecture Provas Científicas da Existência de Deus by Divaldo Franco constitutes the corpus. The oral aspects of this religious discourse are analyzed to verify how the relationship between prosody and argumentation leads to the act of persuading. The research has considered the verbal elements which produce meaning in a discourse which, on the one hand, has the aim of inducing belief based on reasoning, and on the other hand, has a series of elements connected to the emotions. The analysis has as its fundamentals the principles of Phonetics and Phonology, of the New Rhetoric and Theory of Argumentation and of Conversation Analysis. This study made it possible to verify that moroseness and monochordic intonation are constitutive traits of the analyzed lecture. It is also important to note that the prosodic elements, especially volume and speed, give more dynamicity to the lecture, what is most noticeable when the lecturer uses discursive constructions more related to ethos and pathos than to logos. In addition, it can be stated that the prosodic elements together with the argumentative ones lead the text to a more emotional side in contrast with the rational one expressed in semantic terms. Finally, this investigation may contribute to the studies already done in this area and also raise the interest for new researches. Keywords: Prosody; orality; argumentation; spiritis lecture.